2015
DOI: 10.1016/j.jpag.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Fasting Glucose Changes in Adolescents with Polycystic Ovary Syndrome Compared with Obese Controls: A Retrospective Cohort Study

Abstract: Objective To compare changes in fasting glucose among adolescents with polycystic ovary syndrome (PCOS) to obese adolescents without PCOS. Methods Retrospective cohort study of 310 adolescents with PCOS and 250 obese adolescents, (ages 13–18 years) seen at Mayo Clinic, Rochester MN, from 1996–2012. Included for analysis were 98 adolescents with PCOS and 150 obese adolescents who had 2 or more fasting glucose measurements separated by at least 6 months. Adolescents with impaired fasting glucose or diabetes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 45 publications
(26 reference statements)
1
9
0
Order By: Relevance
“…One study (Table 3b) showed that conversion rates from normal glucose tolerance (NGT) to IGT were not significantly different between women with PCOS and controls 32 . In another study, women with PCOS had a significantly higher prevalence of IGT than those without PCOS at baseline, but the prevalence was similar at follow up in both groups 44 . Of the studies that compared the change in glycaemic status based on oral glucose tolerance test (OGTT) within the PCOS group, two studies 32,47 indicated a significant increase in the 2‐h glucose levels from baseline, but one study 40 showed no significant change in the 2‐h glucose levels.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…One study (Table 3b) showed that conversion rates from normal glucose tolerance (NGT) to IGT were not significantly different between women with PCOS and controls 32 . In another study, women with PCOS had a significantly higher prevalence of IGT than those without PCOS at baseline, but the prevalence was similar at follow up in both groups 44 . Of the studies that compared the change in glycaemic status based on oral glucose tolerance test (OGTT) within the PCOS group, two studies 32,47 indicated a significant increase in the 2‐h glucose levels from baseline, but one study 40 showed no significant change in the 2‐h glucose levels.…”
Section: Resultsmentioning
confidence: 98%
“…Characteristics of studies included in this review are outlined in Table 1. Seven of the studies were conducted in the United States, 27,36,39–41,44,56 six in Italy, 29–31,38,48,49 three studies in Iran, 26,45,50 three in Sweden 37,51,52 and each of the remaining 12 studies were conducted in Australia, 53 the Netherlands, 28 Denmark, 54 Turkey, 32 Bosnia, 55 Thailand, 46 Venezuela, 43 Spain and Germany, 35 Croatia, 34 Poland, 42 Korea 33 and Hong Kong 47 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations